Nonlinear pricing and competition intensity in a Hotelling-type model with discrete product and consumer types - Hernandez, Manuel A. (Elsevier, 2011)
This paper develops a Hotelling model with discrete product and consumer types. We analyze the impact of horizontal differentiation (competition intensity) on relative prices. We find that the optimal price ratio of high- to low-quality products decreases with less competition.